Ľ Exploration scientifique de Ľ Afrique au XIXe siècle est-elle une entreprise gégraphique? - Surun, Isabelle (Finisterra, 1998)
WAS 19th CENTURY SCIENTIFIC EXPLORATION OF WEST AFRICA A GEOGRAPHICAL ENTREPRISE? - In the nineteenth century, explorers of West Africa and geographers became involved in crossed scientific relationship. This paper enphasizes the upcoming gap between the scientific aims that geographers and explorers assumed. Geographers focused their investigations on location matters in order to map out traveler's routes through unknown countries, and thus give geographical images of the inner parts of Africa. In the meantime, explorers appeared to be the initiators of an actual human geography of Africa. Their work contributed to convey new paradigms into the geographical field better than the geographers had